1999
DOI: 10.1073/pnas.96.4.1639
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing in Escherichia coli , Salmonella typhimurium , and Vibrio harveyi : A new family of genes responsible for autoinducer production

Abstract: In bacteria, the regulation of gene expression in response to changes in cell density is called quorum sensing. Quorum-sensing bacteria produce, release, and respond to hormone-like molecules (autoinducers) that accumulate in the external environment as the cell population grows. In the marine bacterium Vibrio harveyi two parallel quorum-sensing systems exist, and each is composed of a sensor-autoinducer pair. V. harveyi reporter strains capable of detecting only autoinducer 1 (AI-1) or autoinducer 2 (AI-2) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
696
0
10

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 879 publications
(713 citation statements)
references
References 18 publications
7
696
0
10
Order By: Relevance
“…As brine shrimp larvae are transparent, using bioluminescence as a read-out of quorum sensing activity allowed us to perform this kind of analysis. Quorum sensing-regulated bioluminescence has been used before in many studies investigating the quorum sensing activity of Vibrio harveyi (Bassler et al, 1994;Freeman and Bassler, 1999;Surette et al, 1999;Lilley and Bassler, 2000;Mok et al, 2003;Henke and Bassler, 2004b). We found that the bacteria behave remarkably similar in different larvae, despite the fact that only half of them survive the infection.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…As brine shrimp larvae are transparent, using bioluminescence as a read-out of quorum sensing activity allowed us to perform this kind of analysis. Quorum sensing-regulated bioluminescence has been used before in many studies investigating the quorum sensing activity of Vibrio harveyi (Bassler et al, 1994;Freeman and Bassler, 1999;Surette et al, 1999;Lilley and Bassler, 2000;Mok et al, 2003;Henke and Bassler, 2004b). We found that the bacteria behave remarkably similar in different larvae, despite the fact that only half of them survive the infection.…”
Section: Introductionmentioning
confidence: 76%
“…Vibrio harveyi strains and growth conditions Wild-type strain BB120 (ATCC BAA-1116) and quorum sensing mutants BB152 (luxM::Tn5; Bassler et al, 1994), MM30 (luxS::Tn5; Surette et al, 1999), JMH603 (cqsA::Cm R ; Henke and Bassler, 2004b) and JAF548 (luxO D47E linked to Kn R ; Freeman and Bassler, 1999) were grown in Luria-Bertani medium containing 35 g l À 1 Instant Figure 1 The Vibrio harveyi quorum sensing system. The LuxM, LuxS and CqsA enzymes synthesise the autoinducers HAI-1, AI-2 and CAI-1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…AI-2 levels in the culture supernatants of F. nucleatum, P. intermedia and P. nigrescens were evaluated using the Vibrio harveyi reporter strain BB170 (kindly provided by Dr. Bassler, B.L., Princeton University) as described by Surette et al (27,28). Briefly, after incubation in an anaerobic chamber for 24 hr, each culture broth was centrifuged at 10,000 g for 20 min.…”
Section: Detection Of Ai-2mentioning
confidence: 99%
“…When the concentration of the autoinducers reaches a threshold, an alteration of gene expression is induced, allowing the bacteria to adopt behaviors that are only productive when the bacteria are working together as a group [3,4]. Among many different mechanisms for QS by bacteria, one is shared by both gram-negative and gram-positive bacteria, involving the production of autoinducer 2 (AI-2) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, AI-2 production was verified in a large number of species and the AI-2 QS system was recognized to be involved in the regulation of a range of functions in diverse bacteria [6,7,10,[12][13][14]. In contrast to other autoinducers that are specific for a narrow range of organisms, the widely conserved AI-2 has been hypothesized to be a universal language for interspecies communication [6,9,10,13,15]. In every case, AI-2 is synthesized by LuxS, which functions in the pathway for metabolism of S-adenosylmethionine (SAM), a major cellular methyl donor.…”
Section: Introductionmentioning
confidence: 99%